Knowing Your Limits: A Qualitative Study of Physician and Nurse Practitioner Perspectives on NP Independence in Primary Care - Kraus, Elena (J Gen Intern Med, 2016)
BACKGROUND: The shortage of primary care providers and the provisions of the Affordable Care Act (ACA) have spurred discussion about expanding the number, scope of practice (SOP), and independence of primary care nurse practitioners (NPs). Such discussions in the media and among professional organizations may insinuate that changes to the laws governing NP practice will engender acrimony between practicing physicians and NPs. However, we lack empirical, descriptive data on how practicing professionals view NP independence in primary care. OBJECTIVE: The aim of the present study was to explore and describe the attitudes about NP independence among physicians and NPs working in primary care. DESIGN: A qualitative study based on the principles of grounded theory. PARTICIPANTS: Thirty primary care professionals in Missouri, USA, including 15 primary care physicians and 15 primary care NPs. APPROACH: Semi-structured, in-depth interviews, with data analysis guided by grounded theory. KEY RESULTS: Participants had perspectives that were not well represented by professional organizations or the media. Physicians were supportive of a wide variety of NP roles and comfortable with high levels of NP independence and autonomy. Physicians and NPs described prerequisites to NP independence that were complementary. Physicians generally believed that NPs needed some association with physicians for patient safety, and NPs preferred having a physician readily accessible as needed. The theme “knowing your limits” was important to both NPs and physicians regarding NP independence, and has not been described previously in the literature. CONCLUSIONS: NP and physician views about NP practice in primary care are not as divergent as their representative professional organizations and the news media would suggest. The significant agreement among NPs and physicians, and some of the nuances of their perspectives, supports recommendations that may reduce the perceived acrimony surrounding discussions of NP independent practice in primary care. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-016-3896-7) contains supplementary material, which is available to authorized users.